Features of the constituent process in the activity of the Ministry of Internal Affairs of Ukraine - D. V. Slynko (Law and Safety)
The constituent process as a kind of legal process has been researched. Its specific features in the activity of the Ministry of Internal Affairs of Ukraine include the fact that it is the result of legal regulation, not related to the existence of a dispute about the right; consists of a certain sequence of proceedings (in regard to agencies and units – creation, reorganization and liquidation, in regard to officials – appointment and removal); aimed at the formation, development and improvement of the institutional and personnel basis of the Ministry of Internal Affairs; acts as a special regulatory procedure for carrying out management activity of the implementation of the relevant legal norms; ensures the effective functioning of the state administration mechanism in the relevant field.